2022
DOI: 10.1039/d1rp00313e
|View full text |Cite
|
Sign up to set email alerts
|

Teaching stereoisomers through gesture, action, and mental imagery

Abstract: Many undergraduate chemistry students struggle to understand the concept of stereoisomers, molecules that have the same molecular formula and sequence of bonded atoms but are different in how their atoms...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 87 publications
(106 reference statements)
0
11
0
Order By: Relevance
“…While robust effects of gestures have been found in the domain of mathematical equivalence (e.g., Cook et al, 2013), and there is also evidence for effects of gesture on foreign word learning (e.g., Sweller et al, 2020), there are other cases where gesture does not appear to improve recall or performance (e.g. Guarino & Wakefield, 2020; Ping et al, 2022). Steffens et al (2015) present a list of comparisons between action performance and observation, in which over a dozen studies show no benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While robust effects of gestures have been found in the domain of mathematical equivalence (e.g., Cook et al, 2013), and there is also evidence for effects of gesture on foreign word learning (e.g., Sweller et al, 2020), there are other cases where gesture does not appear to improve recall or performance (e.g. Guarino & Wakefield, 2020; Ping et al, 2022). Steffens et al (2015) present a list of comparisons between action performance and observation, in which over a dozen studies show no benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Steffens et al (2015) present a list of comparisons between action performance and observation, in which over a dozen studies show no benefit. Similarly, while Stieff et al (2016) found that gesture helped students understand chemical molecules, a study directly comparing gesture instruction to action on a molecule and mental imagery (Ping et al, 2022) found no benefit for gesture relative to other kinds of training (see also DeSutter & Stieff, 2020; Rollinde et al, 2021). And studies failing to find an effect are harder to publish than those showing an effect.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable research also shows the role gesture has in reasoning and cognition. ,, In chemistry education research, there has been an effort focused on gesture and problem-solving tasks in organic chemistry. For example, Ping and co-workers examined how students used gesture when mentally manipulating stereoisomers and generating a given compound’s stereoisomer (if one existed) . Stieff, Lira, and Scopelitis demonstrated that gesture can support students when tasked with translating between Newman, Fischer, and dash-wedge representations comparable to using a model kit …”
Section: Literature Frameworkmentioning
confidence: 99%
“…Our work draws on the framework of embodied cognition, which has been used in education research in chemistry, 21,22 physics, 23,24 and mathematics. 25 The central premise of embodied cognition is that learning and thinking about the world "••• is grounded in the interactions our bodies••• have with the world around us."…”
Section: ■ Literature Framework Embodied Cognitionmentioning
confidence: 99%
“…30,31 Investigations in this area also highlight the need for a critical analysis of teacher-centered versus student-centered instructional strategies used to guide students in the unpacking/packing of chemical representations. 28,108 Existing research in chemistry education has shown the positive effects that different types of tasks, such as comparecontrast 109 and drawing activities 13,25 as well as tasks that take advantage of adaptive technologies 110 or embodied cognition 111,112 (e.g., gestures, simulated action), have on different aspects of students' representational competency in chemistry. These investigations, however, typically do not consider how the distinctive characteristics and dimensions of different chemical representations interact with task characteristics to affect student performance.…”
Section: ■ Conclusion and Implicationsmentioning
confidence: 99%